Clay–rock fracturing risk assessment under high gas pressures in repository systems. Issue 1 (1st January 2023) - Mollaali, Mostafa; Buchwald, Jörg; Montoya, Vanessa; Kolditz, Olaf; Yoshioka, Keita
Abstract: At the interface between the steel canister and the bentonite in a nuclear waste repository, we expect generation of hydrogen gas because of corrosion processes. The pressurized gas might fracture the engineered or natural clay barrier system, enhancing radionuclide transport into the geosphere. To assess the long-term integrity of the clay host rock under various conditions and scenarios, we need a large number of numerical simulations. However, a simulation tool for complex fracture propagation is often prohibitively expensive to run many realizations. Here, we developed a risk analysis tool based on the Design of Experiments to overcome the computational challenges by generating a computationally inexpensive proxy fracture model using a set of critical factors known as heavy hitters. We provided parameters and their probability distributions that are subject to uncertainty, as well as an objective function that assesses the risk of fracturing due to high gas pressures. Through various scenarios, we found that the fracture toughness dominates the impact on the risk.